(untitled) (Bangladesh Journal of Botany, 2023)
Abiotic stress tolerant germplasms of field crops are useful for cultivation under growth limiting conditions. In the present study 18 different rice germplasms for their cell membrane injury (CMI), cell membrane stability (CMS), ATPase activity and their relevance to seed germination and seedling growth tolerance index (TI) under abiotic stresses like salinity and low Ψw were investigated. At least 12 germplasms had relatively low membrane injury (< 10%) and consequently high membrane stability (> 90) including TM-1-5, Sadachikon, SR x P 5222, BR 23, Pokkali, Nonabokra, etc. indicating a relationship between stress tolerance and CMS. ATPase activities in some of these rice germplasms were high along with CMS related to stress tolerance. The TI of seed germinations and seedling growth of different germplasms under salinity stress were affected in different degrees and decreased more under high intensities. At 0.l Molal NaCl all germplasms had ≤ 80% TI of seed germination, at 0.2 Molal NaCl only three had ≥ 80% TI and ten had ≥ 50% TI and at 0.3 Molal NaC1, only nine had 10-32% TI and the rest nine did not germinate. Osmoticum PEG-6000 at -5.5 bar Ψw had limited inhibitory effect on seed germination TI. NaCl as well as PEG-6000 degraded both the root and shoot growth TI of the seedlings. Bangladesh J. Bot. 52(3): 889-896, 2023 (September)